Positive Cooperativity Induced by Interstrand Interactions in Silver(I) Complexes with α, α′‐Diimine Ligands. Issue 42 (21st June 2022) - Zare, Davood; Piguet, Claude; Prescimone, Alessandro; Housecroft, Catherine E.; Constable, Edwin C.
Abstract: The allosteric positive cooperativity accompanying the formation of compact [Cu I (α, α′‐diimine)2 ] + building blocks contributed to the historically efficient synthesis of metal‐containing catenates and knotted assemblies. However, its limited magnitude can easily be overcome by the negative chelate cooperativity that controls the overall formation of related polymetallic multistranded helicates and grids. Despite the more abundant use of analogous dioxygen‐resistant [Ag I (α, α′‐diimine)2 ] + units in modern entangled metallo‐supramolecular assemblies, a related thermodynamic justification was absent. Solid‐state structural characterizations show the successive formation of [Ag I (α, α′‐diimine)(CH3 CN)][X] and [Ag I (α, α′‐diimine)2 ][X] upon the stepwise reactions of α, α′‐diimine=2, 2′‐bipyridine (bpy) or 1, 10‐phenanthroline (phen) derivatives with AgX (X=BF4 −, ClO4 −, PF6 − ). In room‐temperature, 5–10 mM acetonitrile solutions, these cationic complexes exist as mixtures in fast exchange on the NMR timescale. Spectrophotometric titrations using the unsubstituted bpy and phen ligands point to the statistical (=non‐cooperative) binding of two successive bidentate ligands around Ag I, a mechanism probably driven by the formation of hydrophobic belts, that overcomes the unfavorable decrease in the positive charge borne by the metallic cation. Surprisingly, the addition of methyl groups adjacent to the nitrogen donors (6, 6′ positions in dmbpy; 2, 9 positions in dmphen) induces positive cooperativity for the formation of [Ag(dmbpy)2 ] + and [Ag(dmphen)2 ] +, a trend assigned to additional stabilizing interligand interactions. Adding rigid and polarizable phenyl side arms in [Ag(Brdmbpy)2 ] + further reinforces the positively cooperative process, while limiting the overall decrease in metal–ligand affinity. Abstract : Big softie : Ag I ([Kr]4d 10 ) possesses similar electronic structure to Cu I ([Ar]3d 10 ), but a larger ionic radius and increased covalency when bound to soft α, α′‐diimine ligands. Consequently, the thermodynamic formation of unsaturated [Ag I (α, α′‐diimine)] + complexes is favored in organic solvents. Moreover, the addition of a second bidentate ligand to give saturated pseudo‐tetrahedral [Ag I (α, α′‐diimine)2 ] + building blocks is driven by positive allosteric cooperativity when the ligands are decorated with terminal methyl groups.